Diffusion Mixed-Node Recursive Least Square-based Algorithm over Adaptive Network - Suchada Sitjongsataporn; Sethakarn Prongnuch; Theerayod Wiangtong (2022 International Electrical Engineering Congress (iEECON), 2022)
This paper proposes a diffusion framework related on the mixed-node constraint based on recursive least squares (RLS) algorithm with adaptive network. The proposed Combine-Then-Adapt and Adapt-Then-Combine diffusion algorithms based on RLS algorithm are derived shortly by minimising the mixed-node least square-based criterion for distributed estimation over the adaptive network. The mixed-node cost function is described and illustrated briefly. Experimental results depict that these proposed algorithms is able to achieve the fast convergence better than the conventional algorithms.
Keywords: Advanced Adaptive Filtering Techniques; Blind Source Separation Techniques; Speech and Audio Processing